Centro Administrativo Municipal De Ibagué (2022)
The objective of this degree work is the architectural design of the Municipal Administrative Center of the city of Ibague, which includes the municipal mayor's office with its different dependencies, which will be carried out in order to improve the efficiency of municipal management in the city, since it presents great limitations of equipment infrastructure for the employees of the municipality that presents an insufficiency in the municipal management and the attention to the citizen, gathering the administrative dependencies in a single building to be able to improve in the development of the labor activities and the citizen can access the facilities in a harmonic way without affecting the quality of the service.